The use of surface wave methods in terrain suceptible to shallow land slides in the city of Campos do Jordão, Brazil - Shams, Brian Sam (2016)
This study seeks to prove the usefulness of the Multichannel Analysis of Surface Waves (MASW) method as complementary data to conventional geotechnical and geological data in the characterization of areas of landslide risk. The setting is located in a low income housing neighborhood in the city of Campos do Jordão, state of São Paulo, Brazil. The area was devastated by numerous landslides between December 1999 to January 2000 after heavy rainfall in the area. The landslides in this area are known to be shallow. Refraction and MASW surveys were performed in this research and then processed to obtain seismic velocity profiles of the subsurface. In order to better identify the fundamental mode of the Rayleigh wave, separate surveys isolating the vertical and radial components of the Rayleigh wave were performed. By comparing the inverted shear wave ( ) and compressional wave ( ) profiles with the already known geotechnical and geological data of the site, a better understanding of the geological interfaces that constitute the landslide prone area is obtained.